Redes de comercialização de peixes in natura nas feiras livres municipais de Palmas - TO - Júlio, Ingrid Gianotti (Universidade Federal do Tocantins, 2016)
This research aims to know the networks currently established by fish traders in natura in municipal fairs of Palmas-TO, in order to identify the economic agents involved, the main species tendered and investigate the conditions of direct marketing to the final consumer, highlighting the hygiene and health aspects. Therefore, it started with the secondary survey and field research, using structured interviews, direct observation script and photographic record. This commercial activity in free markets involves different economic agents, both upstream like the downstream. Upstream, suppliers agents associated with fishing (fishers of Palmas, Porto Nacional, Caseara, Bananal Island, Tocantins, and Belém, Santarém, Tucuruí and São Félix do Xingu, Pará), aquaculture (fish farmers of Lajeado, Porto Nacional and Fátima in Tocantins), the fish slaughterhouse (Almas and Nazareth Brejinho in Tocantins) and one retailer in Palmas-TO; and the fairground, in turn, supply, in addition to final consumers in the markets, traders in Palmas and in cities of Pará. It is noteworthy that the marketing of fish in natura in the fairs there are problems with respect to sanitary conditions, especially in with regard to facilities, equipment, storage, handling and others. In short, these marketing networks of in natura fish involving the fairs in Palmas feature local and regional level, involving two states of the Federation (Tocantins and Pará) and have your settings changed by the closure period of fishing for the spawning season (November to February) and for informality of the business relationship.